The Effect of Profitability, Liquidity, Leverage and Company Size on Sukuk Yield With The Rating of Sukuk as Intervening Variables - Syakdiyah, Karimatus; Putra, Purnama (El-Qish: Journal of Islamic Economics, 2021)
The purpose of this study was to test whether profitability, liquidity, leverage, and company size affect the yield of Sukuk with the Sukuk rating as an intervening variable. The method chosen to conduct this research is a quantitative method in which the data is processed using path analysis The data used in this research is secondary data. The sample used is 12 companies for the period 2012-2017. Findings. The results of this study can be concluded that partially profitability has a significant positive effect, liquidity has a significant negative effect, leverage has no effect and is not significant, company size has a significant positive effect on the sukuk rating. While profitability has a significant negative effect, liquidity has no and insignificant effect, leverage has a significant negative effect, company size has no and insignificant effect, sukuk rating has no and insignificant effect on sukuk yield. The sukuk rating cannot mediate the profitability and leverage variables on the sukuk yield. However, the sukuk rating can mediate the liquidity variable and company size on the sukuk yield.